Crystal structure of FhuD at 1.6 Å resolution: a ferrichrome‐binding protein from the animal and human pathogen Staphylococcus pseudintermedius. Issue 3 (2nd March 2016) - Abate, Francesca; Cozzi, Roberta; Maritan, Martina; Lo Surdo, Paola; Maione, Domenico; Malito, Enrico; Bottomley, Matthew James
Abstract : The crystal structure of the FhuD protein from S. pseudintermedius was determined at 1.6 Å resolution. The structure displays a canonical class III solute‐binding protein fold in a closed conformation, revealing a ligand‐binding site suitable for the accommodation of siderophore ligands, here occupied by a polyethylene glycol molecule. Abstract : Staphylococcus pseudintermedius is a leading cause of disease in dogs, and zoonosis causes human infections. Methicillin‐resistant S. pseudintermedius strains are emerging, resembling the global health threat of S. aureus . Therefore, it is increasingly important to characterize potential targets for intervention against S. pseudintermedius . Here, FhuD, an S. pseudintermedius surface lipoprotein implicated in iron uptake, was characterized. It was found that FhuD bound ferrichrome in an iron‐dependent manner, which increased the thermostability of FhuD by >15°C. The crystal structure of ferrichrome‐free FhuD was determined via molecular replacement at 1.6 Å resolution. FhuD exhibits the class III solute‐binding protein (SBP) fold, with a ligand‐binding cavity between the N‐ and C‐terminal lobes, which is here occupied by a PEG molecule. The two lobes of FhuD were oriented in a closed conformation. These results provide the first detailed structural characterization of FhuD, a potential therapeutic target of S. pseudintermedius .